Didactic Resources to Strengthen the Division of Natural Numbers through a Sequence of Didactic Activities (Docentes 2.0 Journal, 2021)
Within the curriculum, the fifth-grade mathematics subject is oriented under the Escuela Nueva methodology. The objective of this research was the design of teaching resources, applied through a teaching unit for fifth-grade students of the Padua Educational Institution in the municipality of Onzaga, Santander. To strengthen the research process, an international, national and local bibliographic review was carried out; this was of great help to carry out the methodological design. The type of research of the project was qualitative with an action research approach. The methodology used was developed considering that this student population is from a rural area. They have the new school model, which was managed together with the educational alternation model adopted by the MEN during this health crisis caused by COVID-19. This methodology consists of an entrance test, followed by a didactic unit designed with three work sessions. An exit test, all of them based on moralistic and didactic situations raised by Brousseau. Next, collected information. The analysis of results according to the categories used and concluded that applying the theory of didactic and didactic conditions of Brousseau allowed strengthening the teaching-learning process for the processes of division, likewise contributed so that can replicate its application to other areas of knowledge.
Keywords: Math; a-didactic situation; didactic situation; Guy Brosseau